1997
DOI: 10.1183/09031936.97.10081703
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary perspective: immunology in diagnosis and treatment of lung cancer

Abstract: Finally, the discovery of several tumour rejection antigens has revived the dream of designing tumour vaccines and active specific immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 184 publications
(171 reference statements)
1
15
0
2
Order By: Relevance
“…One of the major sources are alveolar macrophages (AMs) [23]. Suppression of AMs in the course of lung cancer was observed by others [30]. In our study, negative correlation of TGF-β1 level with the proportion of AMs was found.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…One of the major sources are alveolar macrophages (AMs) [23]. Suppression of AMs in the course of lung cancer was observed by others [30]. In our study, negative correlation of TGF-β1 level with the proportion of AMs was found.…”
Section: Discussionsupporting
confidence: 70%
“…In our study, negative correlation of TGF-β1 level with the proportion of AMs was found. TGF-β as a product of tumor cells has a potent immunosuppressive effect on AMs [18,30]. As was shown in a study by Bingisser et al [5], TGF-β may down-regulate apoptosis of alveolar macrophages, and the possible negative feedback may be induced by AMs themselves.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Study of tumor-associated antigens (TAA) detected in cancer patients and their role in the diagnosis and treatment of malignant tumors is an important trend of cancer research [3]. TAA are high-molecular-weight glycoproteins with extremely conservative structure, which may be indicative of their important biological role.…”
Section: Abstract: Natural Autoantibodies; Human Ovarian Cancer; Murmentioning
confidence: 99%
“…mutated or overexpressed oncogene products or differentiation anticens (Boon. 1997: Wevnants. 1997 Miller (1979) Oral 308 No benefit McKneally (1981) Intrapleural 169 Improved survival (stage 1) Mountain (1981) Table 2. EL-2 used alone or in combination xxith other cvtokines or ly mphokine-actixated killer (LAK) cells in phase II trials in NSCLC has induced some responses (Table 3).…”
Section: Tumour Immunologymentioning
confidence: 99%